Mecanismos para la mitigación del cambio climático en los países andinos: un enfoque amazónico - León Arellano, Tristán Augusto (2024)
United Nations Framework Convention on Climate Change begins the constitution of a global institutionality in this matter, that has been developing in the last decades, through complementary treaties as the Kioto Protocol, Paris Agreement and the successive decisions, approved in the Conference of the Parties of those treaties. The review of the institutions, agreements and statements approved in the scope of the Convention and the complementary treaties, allows to determine the current rules in the matter and to appreciate the urgency to advance in the global mitigation in the emission of greenhouse gases, pointed out for the scientific community, as the cause of the accelerated climate change. In that sense, this text reviews the posibilities, of a join action in mitigation matters in the andean region, in order of the importance that corresponds a climate action in the andean countries, specifically in those that share the amazon forest, one of the most importants natural greenhouse gases sinks of the world. Additionally this text proposes the aplication of the market mitigation mechanisms, in a joint action between Colombia and Peru (suggesting to add Ecuador), considering as the first step the aplication of the carbon tax, in the outlook to build a joint policy that could extend to other market mitigation mechanisms, considering too, the possibility of a future agreement with Brasil, focusing to include as a strategic factor, the shared geography of the amazon basin.